2021
DOI: 10.1016/j.jtcvs.2019.09.184
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgical aortic valve replacement on quality of life—a multicenter study

Abstract: Objectives: To explore the effect of surgical aortic valve replacement on quality of life and the variance with age, particularly in patients at risk of deterioration.Methods: In an observational, multicenter, cohort study of routinely collected health data, patients undergoing and electively operated between January 2011 and January 2015 with pre-and postoperative quality of life data were included. Patients were classified into 3 age groups: <65, 65-79, and !80 years. Quality of life was measured at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…In a more selected group of high-risk patients with an indication for either surgical aortic valve replacement or transcatheter aortic valve implantation, an absence in increased physical performance at 6-months was as high as 58.7% [19]. Our data do not confirm age as independent risk factor, as previously reported in the setting of elective CABG and aortic valve replacement [20,21]. This may be due to differences in inclusion criteria (our study also reports on non-elective surgery patients) or the fact that age was included in our multivariate model as a continuous, rather than a categorical variable.…”
Section: Discussioncontrasting
confidence: 60%
“…In a more selected group of high-risk patients with an indication for either surgical aortic valve replacement or transcatheter aortic valve implantation, an absence in increased physical performance at 6-months was as high as 58.7% [19]. Our data do not confirm age as independent risk factor, as previously reported in the setting of elective CABG and aortic valve replacement [20,21]. This may be due to differences in inclusion criteria (our study also reports on non-elective surgery patients) or the fact that age was included in our multivariate model as a continuous, rather than a categorical variable.…”
Section: Discussioncontrasting
confidence: 60%
“…To assess the level of implementation of MCID methodology in cardiothoracic (CT) surgery, six studies were identified through the thorough literature search and were included that employed the MCID methodology to assess QoL in those patients ( Table 1 ) [ 12 , 20 , 21 , 22 , 23 , 24 ]. The first study employed anchor-based methods to calculate MCID metrics [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study [ 20 ] evaluated the association of surgical aortic valve replacement (SAVR) and QoL, along with the variance with age, especially for high-risk patients. This was an observational, multicenter cohort study that was conducted in accordance with the RECORD guidelines (Reporting of studies Conducted using Observational Routinely collected Data) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advancement in the diagnosis and treatment of valvular heart disease is one of the greatest medical achievements of the 20th century, one that continues to advance today. Aortic Valve Replacement (AVR), in particular, significantly improves patient quality of life (QOL) and is associated with increased survival in patients with severe aortic stenosis (AS) 1–3 . Surgical AVR (SAVR), first performed in 1967, has been used to treat millions of patients worldwide.…”
Section: Introductionmentioning
confidence: 99%